Report of the Greek and Italian Youth Employment Study - Young, Christabel; Australian National University; Australia. Department. of Immigration and Ethnic Affairs ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
The results of a study which identified the employment aspirations and needs of Greek and Italian immigrant youth in Australia are presented in this book. There are 11 Chapters, the first three of which discuss, respectively; (1) research background and methodology; (2) the experience of Greek and Italian immigrant youth in Australia (a literature review); and (3) characteristics of the teenage immigrant labor force (an analysis of 1976 Census data regarding the schooling and employment of immigrant youth in Australia). Chapters 4 through 8 discuss and analyze the following demographic data; (4) ethnic language, participation, and identity; (5) the school experience; (6) the workforce experience; (7) durations of unemployment and continuous employment; and (8) job aspiration, generational change, and comparisons between geographically different samples. Chapter 9 discusses the development of a set of measures to determine attitudes to work; and Chapter 10 presents the analysis and results of the attitude measures. The final chapter is a summary and discussion of the implications of the study as a whole. (KH)
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Demography; Educational Attainment; Educational Experience; Employment Patterns; Ethnic Groups; Ethnicity; Foreign Countries; Immigrants; Labor Force; Minority Groups; Non English Speaking; Occupational Aspiration; Secondary Education; Unemployment; Work Attitudes; Youth Employment; Greek Australians -- Italian Australians; Australia; Reports, Research; Numerical/Quantitative Data